Macroeconomic theory - Ackley, Gardner (New York: Macmillan, 1961)
The book is a product of some fourteen years of teaching a semester course "The National Income" at the University of Michigan by the author. The text is aimed at undergraduates and first-year graduate students. The book is primarily theoretical and attempts to develop the relevance of the theory to the diagnosis of current economic conditions and to current discussions of public policy, but has also at some points introduced empirical matters. It is divided into four parts: Concepts and Measurements; The Classical Macroeconomics; The Keynesian Macroeconomics and Some Extensions.
Published in 1978 under title: Macroeconomic analysis and theory.
rpm 27/09/2017
Loans
Keywords: Macroeconomics